The Implementation of Health Education about Diabetic Foot Care among Patiens with Diabetes Mellitus to Improve Patients Knowledge: A Literature Review - Darni, Zahri; Agustin, Shynta Amelia (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2023)
Diabetes Mellitus (DM) is a chronic disease that occurs due to metabolic disorders and is characterized by blood sugar levels that exceed normal limits. Complications of DM if not treated immediately can cause peripheral neurophaty, namely loss of sensation in the feet. Peripheral neuropathy prevention measures by performing foot care that can be provided through health education by nurses. The purpose of this literature review is to get an overview of the implementation of health education in an effort to increase knowledge of DM foot care in an empirical study of the last 10 years. The article search method uses for databases through Scient Direct, ProQuest, E-Resources National Library and Google Scholar (2011-2021) using Indonesian and English according to the inclusion criteria. Study design using cross sectional design and systematica/literature review. The results of a literature review of 7 articles consist of 3 articles of knowledge type and 4 articles of health education which stated that Ha or the alternative hypothesis was accepted. The conclusion from this literature review is that the implementation of health education about DM foot care can increase patient knowledge. It is recommended that nurses can maintain the implementation of health education to increase patient knowledge.